THE ECONOMETRIC ANALYSIS OF THE EXPORTS AND FOREIGN EXCHANGE RATES IMPACT ON WINE PRODUCTION: THE CASE OF ARMENIAN WINE INDUSTRY - Felix H. ARION; Karlen KHACHATRYAN; Vardan ALEKSANYAN; Hovhannes ASATRYAN (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
This article uncovers relationships between the wine export and production in Armenia. Wine industry is a strategically important economic sector in Armenian. The importance of its development is strongly supported by the fact that alcoholic beverages from grape processing are products with high customs value exported from Armenia (in 2020 the share of alcoholic beverages in the entire export structure was about 8.4%). Within the framework of this study, a detailed analysis of the wine production was performed. By applying econometric analysis, we assessed the impact that the increase of wine export has on wine production. Also, the empirical analysis of the impact of USD and RUB exchange rates on wine industry was performed. Overall, the econometric analysis indicated that export volumes and USD exchange rate significantly affect Armenian wine industry. This study provides enough evidence for us to conclude that the export of Armenian wine must be heavily promoted by Government policies and the same time the export directions must be diversified. The results of this study can be basis for scientific substantiation of sectorial strategies developed by the Government of Armenia.